Constraints faced by growers in adoption of recommended practices of teak - Khandagale, A.S.; Taide, Y.B.; Deshmukh, H.K.; Thigale, M.B. (Indian Journal of Agroforestry, 2020)
The study was planned to investigate and ascertain the constraints faced by the teak growers in adoption of recommended cultivation practices. Teak growers have planted recommended species of teak at appropriate time. The adoption of intercrops, gap filling, thinning, manures and fertilizers, and plant protection measures were found to be poor. None of the teak growers had used recommended mulching. The teak growers need to be convinced about the usefulness of these practices for healthier plant growth. The literature on teak cultivation in local language should be brought out to equip the teak growers with necessary knowledge. The major constraints faced by the teak growers in adoption of teak plantation were, high prices of fertilizers and plant protection chemicals, non-availability of loan and skilled labour for planting, difficulty in getting information about teak plantation and permission to fell teak plantation. To overcome these constraints, the teak growers suggested for provision of loan and subsidies, keeping the prices of inputs like stumps, fertilizers and insecticides reasonable and withdrawing the compulsion for prior permission to plant and fell teak trees.